Rosa roxburghii Tratt Fruit Juice Ameliorates DSS‐Induced Colitis by Improving Intestinal Barrier and Gut Microbiota Independently of Vitamin C - Wenyue Chen; Dafeng Fang; Lili Zhang; Mingqing Kuang; Mengyao Zhang; Chenxiao Shen; Yi Liu; Hefeng Zhou; Shengpeng Wang; Wenwen Zhao; Yitao Wang; Zhangfeng Zhong (eFood)
ABSTRACT Rosa roxburghii Tratt (Cili) is a vitamin C‐rich fruit with bioactive polyphenols and flavonoids. This study explored the components of Cili fruit juice and investigated its therapeutic potential in a dextran sodium sulfate (DSS)‐induced ulcerative colitis (UC) murine model. Our results revealed that Cili fruit juice and its components (vitamin C and kajiichigaside F1) significantly alleviated colitis symptoms. Notably, colitis symptoms improved even when vitamin C‐deficient Cili juice was administered. Specifically, Cili fruit juice restored intestinal barrier integrity, regulated inflammatory cytokines (TNF‐α, IL‐6, IL‐8, and IL‐12), and modulated gut microbiota dysbiosis by rebalancing Epsilonbacteraeota, Proteobacteria, and Lactobacillus abundances. Furthermore, Cili fruit juice positively modulated cellular metabolic processes and inflammatory pathways. These findings identify Cili fruit juice as a promising natural adjuvant therapy for UC, driven by the potent bioactivity of kajiichigaside F1, offering a novel strategy to enhance intestinal homeostasis and mitigate inflammation.